Relationship between muscular atrophy of the tongue and impairment of bolus transport during swallowing in patients with amyotrophic lateral sclerosis - Yamada, Yoshiaki; Taniguchi, Hiroshige; Inoue, Makoto; Ootaki, Sachiko; Kajii, Yuka (The Journal of Japanese Society of Stomatognathic Function, 2008)
The present study was focused on the tongue atrophy which is one of the common symptom in patients with amyotrophic lateral sclerosis (ALS) and investigated the effects of tongue atrophy on impairment of swallowing function by using videofluorographic assessment. The subjects included 19 patients diagnosed ALS and 11 age-matched normal adults. Each subject was asked to swallow 3 ml water with 40 vt/wt% barium sulfate. Whether aspiration and/or penetration of bolus before, during and after swallowing was observed or not and amount of bolus residues in the pharynx were evaluated. Furthermore, in case of no aspiration observed, bolus transit times were measured and compared among the groups. All the cases in which the patient had an episode of aspiration were related to the muscular atrophy of tongue. The patient group showing tongue atrophy exhibited higher scores of pharyngeal residue than the other groups, meaning that the amount of pharyngeal residues after the swallow in the former group was much more than that of patients with no atrophy of the tongue or normal adults. Comparing the bolus transit time among the atrophic tongue in patients without aspiration, normal tongue in patients and normal adults, Clearance Time, i.e., the time of the bolus invading the pharynx and Upper Esophageal Segment Transit Time were delayed and the bolus head reached at the bottom of hypopharynx before onset of swallowing in the first group. It may be possible that abnormal structure and motility and/or extension of pharyngeal duct due to the atrophy of tongue may cause the difficulty in the bolus handling in the oral cavity and delay of triggering reflex swallowing. All the results obtained in the present study suggested that the muscular atrophy of tongue in patients with ALS may be a critical sign for the risk of severe problem with swallowing function.